A study of perinatal mortality with obstetrics point of view with etiological factors and preventive approach - Upadhyay, Hemangini J.; Ninama, Pallavi G.; Shah, Margi A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Perinatal mortality rate (PNMR) serves as the most sensitive index, directly reflecting prenatal; intrapartum and newborn care. In order to reduce perinatal mortality, it is necessary to study the various factors influencing perinatal deaths. Methods: It was a retrospective study done over the period of 1 year from January 2021 to December 2021. Total 4389 deliveries were included out of which 228 perinatal deaths occurred. Causes of perinatal deaths were identified and studied. Results: Results showed that perinatal mortality rate was 17.5 per 1000 live births. Incidence of early neonatal death was 17.5% per total admissions. Majority of perinatal deaths occurred due to preterm, low birth weight. Maternal factor associated with perinatal mortality were antepartum haemorrhage, eclampsia, obstructed labour, malpresentation, medical problems in pregnancy. Conclusions: The perinatal mortality could be prevented with strengthening of antenatal care screening, educating pregnant women to recognize the signs of complications of pregnancy, timely access to obstetric care, monitoring of labour for fetal distress, and proper newborn resuscitation. With proper coordination of neonatologist and obstetrician, sizeable reduction in perinatal mortality can be achieved.